UMP leaps to 129th best university in Asia - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 2 November 2021 - Universiti Malaysia Pahang (UMP) leaped to 129th spot compared to 133 last year in the QS Asia University Rankings announced by the international rating agency QS Quacquarelli Symonds for 2022.